Effect of Cultivated Species and Planting Pattern on Plant Growth, Soil Properties, and Soil Metabolites in a Rain-Fed Orchard in Gansu, China - Yali Zou; Qi Li; Yuying Shen (Agronomy, 2025)
Orchard cover crops enhance the local microclimate and soil fertility, serving as an eco-friendly, efficient management practice. However, the effects of different cultivated species and planting patterns on plant growth and soil properties remain unclear. In this study, we hypothesized that different cultivated species and planting patterns would differently affect root growth and soil biochemistry. Therefore, the root growth, soil nutrients, and soil metabolites in an orchard planted with Vulpia myuros, Vicia villosa, Orychophragmus violaceus, and Brassica campestris in either a tree-disk or inter-row patterns were conducted. The results indicated that the tree-disk pattern promoted root development. This increase in below-ground biomass contributed to changes in soil nutrient dynamics, with a significant biomass accumulation observed for Orychophragmus violaceus. While the inter-row pattern improved soil aeration and was conducive to aboveground plant growth. The tree-disk pattern with Vicia villosa and Brassica campestris increased the total phosphorus (TP) and total potassium (TK) in the 0–10 cm layer. The soil NH4+-N and NO3−-N contents were higher under the tree-disk pattern than under the inter-row pattern with Brassica campestris, whereas the opposite effect was seen with Vulpia myuros. Overall, we recommend planting Orychophragmus violaceus in a tree-disk pattern and Vulpia myuros in an inter-row pattern to promote plant biomass accumulation and soil nutrient increases in orchards. Our study provides a basis for the selection of orchard-cultivated species and planting patterns to promote the sustainable development of the fruit industry.